Differentiation and imperfectionality in John Updike’s Terrorist - M Ikbal M Alosman,; Raihanah M. M.,; Ruzy Suliza Hashim, (Penerbit Universiti Kebangsaan Malaysia, 2018)
John Updike, one of America’s eminent 20th century novelists, provides his own fictionalized presentation of the Muslim other within the American socio-cultural context in his 22nd novel, Terrorist. This novel is abundant with binary representations of Muslims whose acts and interactions with fellow Christian and Jewish Americans are scripted by their respective religious values. Updike’s exemplifications of Islam and Muslims within the American context are investigated through the problematizing of Muslims’ socio-cultural imperfections within the lens of orientalism and psychology of (im)perfection. Imperfectionalism as used in this paper refers to the inconsistent, unreliable and unpredictable characteristics that define the Muslim Other in comparison to mainstream American society. Using themes of ‘religious differences,’ ‘differences between religions,’ ‘social differences,’ ‘gendered and exotic differences’ and ‘optimized differences,’ Updike’s Muslim characters are presented as flawed and faulty in their beliefs and conviction. In addition, Updike’s representation of Islam rests on its blemishes including its disregard for self-improvement and modernity. Designs of orientalism and imperfection as seen in this novel frame the Muslim other as the imperfect version of the perfect non-Muslim American.